Organizational and Legal Aspects of Fee-based Education in the Republic of Kazakhstan - ALTYNBASOV, Bakhyt O.; MYRZATAYEV, Nurmukhamed; TASTEKEEV, Kairat; SAKTAGANOVA, Indira; OSMANOVA, Dinara (Journal of Advanced Research in Law and Economics, 2017)
The education system characteristics of the Republic of Kazakhstan were discussed and peculiarities of education on different levels were considered in this article. Advantages and disadvantages of fee-based education for the state and society were given. Comparative analysis of fee-based education development was made. The role of fee-based education in national human capital formation was examined. The state and society elite and human potential problems were researched. How to apply fee-based education in the current legislation and what negative sides of it exist – all these problems were reviewed in the article. Scientifically substantiated recommendations were made on the research results.